Experimental Study of HCl Capture Using CaO Sorbents: Activation, Deactivation, Reactivation, and Ionic Transfer Mechanism - Sun, Zhenchao; Yu, Fu-Chen; Li, Fanxing; Li, Songgeng; Fan, Liang-Shih (Industrial & engineering chemistry research, 2011)
Experimental study of dry HCl removal from synthesis gas or flue gas using CaO sorbents, in the context of CaO-based chemical looping processes, is reported. The study was first conducted in a TGA and a fixed-bed reactor to test the effects of chloridation temperature, sorbent particle size, HCl concentration, and space velocity on the HCl capture capacity. The chloridation reactivity deterioration of CaO sorbents with multicyclic carbonation−calcination reaction (CCR) and/or at high calcination temperatures, which are of notable relevance to the CaO-based chemical looping processes, was also investigated. In addition, precipitation (activation) and hydration (reactivation) were used to enhance initial sorbent reactivity and to reactivate the deactivated sorbents, respectively. The effects of deactivation, activation, and reactivation were explained by the morphological property change of the sorbents. To further elucidate the solid phase reaction mechanism of CaO and HCl, ionic transfer behavior during chloridation reaction was characterized using an inert marker experiment. Through the present work, the performance of CaO sorbents in HCl capture, deactivation of the sorbents by high-temperature calcination and multiple CCR cycles, sorbent activation and reactivation strategies, and the corresponding reaction mechanisms are determined.